A new species of Hydrochara Berthold from China (Coleoptera, Hydrophilidae, Hydrophilini) - Mai, Zuqi; Jia, Fenglong (Zootaxa, 2024)
A new species of the water scavenger beetle, Hydrochara loong sp. nov. is described based on a pair of specimens collected from Shaanxi and a female collected from Hubei. This new species is similar to Hydrochara libera (Sharp, 1884) in morphology, but with a larger size and some distinct morphological differences. The new species is diagnosed and illustrated in detail. A key to Chinese species of the genus Hydrochara is provided.